Admixture mapping of tuberculosis and pigmentation-related traits in an African–European hybrid cattle population - Kassahun, Yonas; Mattiangeli, Valeria; Ameni, Gobena; Hailu, Elena; Aseffa, Abraham; Young, Douglas B.; Hewinson, R. Glyn; Vordermeier, H. Martin; Bradley, Daniel G. (Frontiers in Genetics, 2015)
Admixture mapping affords a powerful approach to genetic mapping of complex traits and may be particularly suited to investigation in cattle where many breeds and populations are hybrids of the two divergent ancestral genomes, derived from Bos taurus and Bos indicus. Here we design a minimal genome wide SNP panel for tracking ancestry in recent hybrids of Holstein Friesian and local Arsi zebu in a field sample from a region of high bovine tuberculosis endemicity in the central Ethiopian highlands. We first demonstrate the utility of this approach by mapping the red coat color phenotype, uncovering a highly significant peak over the MC1R gene and a second peak with no previously known candidate gene. Secondly, we exploit the described differential susceptibility to bovine tuberculosis between the ancestral strains to identify a region in which Bos taurus ancestry associates, at suggestive significance, with skin test positivity. Interestingly, this association peak contains the toll-like receptor gene cluster on chromosome 6. With this work we have shown the potential of admixture mapping in hybrid domestic animals with divergent ancestral genomes, a recurring condition in domesticated species.